The effect of cut depth and distribution for abrasives on wafer surface morphology in diamond wire sawing of PV polycrystalline silicon. (1st March 2019) - Li, Xinying; Gao, Yufei; Ge, Peiqi; Zhang, Lei; Bi, Wenbo
Abstract: Due to the existence of an acid etch resistant thin amorphous silicon layer over the smooth grooves of the diamond wire sawing polycrystalline silicon wafer surface, the anti-reflection effect is usually not ideal using the mature acidic texturization. The amorphous silicon layer will be produced on the machined surface by material ductile removal. Therefore, during the process of cutting photovoltaic polycrystalline silicon wafers, the material removed in the brittle way is expected and the surface topography of the wafers formed with the brittle fracture is better for the texture fabricating. In this paper, a mathematical model considering the influences of process parameters and wire saw parameters was developed based on indentation fracture mechanics. The variations of cutting groove profile formed by different material removal modes were also included. The effect of abrasives distributed on the wire saw on material removal and surface formation of polysilicon was analyzed. The results showed that most of abrasives removed material with ductile removal mode, however, the volume of the material removed by abrasive in ductile mode is less than 10% of the total removal volume. Brittle fracture removal mode was still the major way of material removal in diamond wire sawing. With the same ratio of the feed rate and wire speed, the faster feed rate and wire speed will not only improve the cutting efficiency, but also is easier to obtain a brittle fracture surface. There is a critical angle θ c for the distribution of abrasives on the wire saw surface. Only when the position angle of the abrasive removing material in brittle mode is less than θ c, the brittle fracture can be formed on the wafers surface.